PENATALAKSANAAN FISIOTERAPI PADA OSTEOARTHRITIS GENU DENGAN MODALITAS TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION DAN TERAPI LATIHAN - Rondonuwu, Nikita; Pombu, Novtiyas (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2022)
Background: Osteoarthritis (OA) is a chronic progressive joint disease, generally found in middle-aged to elderly people, which is characterized by cartilage breakdown in bone joints. Objective: This case study aims to determine the physiotherapy management of genu osteoarthritis to reduce pain and increase functional activity with transcutaneous electrical nerve stimulation (TENS) modalities and exercise therapy. Method: The respondent in this case study is a 40-year-old father at GMIM Bethesda Hospital, Tomohon. Pain assessment using the Verbal Description Scale (VDS) and functional activity with the jette scale. After doing therapy 6 times. Results: the results obtained by giving TENS and Exercise Therapy are as follows, for pain examination, silent pain from 4 to 1, tenderness from 4 to 2 and motion pain from 5 to 3, a decrease in pain intensity and for functional activity examination for squatting to standing activities the pain score was from 4 to 3. The difficulty value was from 4 to 3 and the dependency value was from 3 to 2. from 2 to 1. Then for the 6 meter walking activity the pain value from 3 to 1, the difficulty value from 2 to 1 and the dependency value remains 1, there is an increase in functional activity. Conclusion: The conclusion in this case study is that TENS and exercise therapy can reduce pain and increase functional activity in knee osteoarthritis.